Validation of the Turkish Form of Short Form-12 health survey version 2 (SF-12v2) - Özgül SOYSAL GÜNDÜZ; Senan MUTLU; Arzu ASLAN BASLI; Cihan GÜL; Özgür AKGÜL; Emel YILMAZ; Ömer AYDEMİR (Archives of Rheumatology, 2021)
Objectives: In this present study, we aimed to perform the reliability and validity analyses of the Turkish Form of Short Form-12 version 2 (SF-12v2) in different groups of patients. Patients and methods: After the permission for the validation study of the Turkish Form, Optum provided the authors the validly translated Turkish Form of SF-12v2. The study was carried out in rheumatological, psychiatric, and surgical wards of Manisa Celal Bayar University Hafsa Sultan Training and Research Center between September 2019 and June 2020. Taking possible dropouts into consideration, a total of 136 patients (67 males, 69 females; mean age: 43.5±14.4 years; range 19 to 82 years) constituted the study group. In addition to SF-12v2, for concurrent validity, Nottingham Health Profile (NHP) was used as the comparator instrument. Results: In internal consistency, for the physical component summary score, the Cronbach alpha coefficient was 0.80, and item-total score correlation coefficients were between 0.32 and 0.73. The Cronbach alpha coefficient of the mental component summary score was found to be 0.88 where the item-total correlation coefficients varied between 0.60 and 0.78. Exploratory factor analysis revealed a two-factor solution, representing mental and physical components. For criterion validity, convergent and discriminant validity analyses were performed using NHP with SF-12v2, and domains of SF-12v2 correlated well with the domains of NHP accordingly. In criterion validity, the psychiatric group had the lowest mean score in mental health, vitality, social functioning and role difficulties due to emotional problems, whereas the surgical group had the lowest mean score in bodily pain, role difficulties due to physical problems, and physical functioning. Conclusion: Our study results show that the Turkish form of SF-12v2 is valid and reliable both in clinical practice and clinical trials.